Waist circumference provides an indication of numerous cardiometabolic risk factors in adults with cerebral palsy. - GORMLEY, JOHN (My University, 2014)
OBJECTIVE: To report the prevalence of cardiometabolic risk factors in a cohort of adults with cerebral palsy (CP) and to investigate the ability of anthropometric measures to predict these factors. DESIGN: Cross-sectional study. SETTING: Testing took place in a laboratory setting. PARTICIPANTS: Adults with CP (N=55; mean age, 37.5±13.3 y; Gross Motor Function Classification System levels, I-V) participated in this study. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, glucose, insulin, and C-reactive protein levels were measured from a fasting venous blood sample. Insulin resistance was calculated using the Homeostasis Model Assessment (HOMA-IR) index. Blood pressure, body mass index (BMI), waist circumference (WC), waist-hip ratio, and waist-height ratio were also measured. The metabolic syndrome (MetS) was defined according to the 2009 Joint Interim Statement. RESULTS: The prevalence of the MetS was 20.5% in ambulatory adults and 28.6% in nonambulatory adults. BMI was associated with HOMA-IR only (β=.451; P<.01). WC was associated with HOMA-IR (β=.480; P<.01), triglycerides (β=.450; P<.01), and systolic blood pressure (β=.352; P<.05). Receiver operating characteristic curve analysis revealed that WC provided the best indication of hypertensive blood pressure, dyslipidemia, HOMA-IR, and the presence of multiple risk factors (area under the curve, .713-.763). CONCLUSIONS: A high prevalence of the MetS was observed in this relatively young sample of adults with CP. WC was a better indicator of a number of risk factors than was BMI and presents as a clinically useful method of screening for cardiometabolic risk among adults with CP.
PUBLISHED
Keywords: Body Mss Index